2012
DOI: 10.3390/catal2010085
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Anthracene in Supercritical Carbon Dioxide Solvent Using Ni Supported on Hβ-Zeolite Catalyst

Abstract: Catalytic hydrogenation of anthracene was studied over Ni supported on Hβ-zeolite catalyst under supercritical carbon dioxide (sc-CO2) solvent. Hydrogenation of anthracene in sc-CO2 yielded 100% conversion at 100 °C, which is attributed to the reduced mass transfer limitations, and increased solubility of H2 and substrate in the reaction medium. The total pressure of 7 MPa was found to be optimum for high selectivity of octahydroanthracene (OHA). The conversion and selectivity for OHA increased with an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…It has been reported that Ni is commonly used most in the hydrogenation process, which can form dehydrogenation and hydrogenation sites, being favorable for gas generation …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Ni is commonly used most in the hydrogenation process, which can form dehydrogenation and hydrogenation sites, being favorable for gas generation …”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from Figure a, the decrease of tar yield and the increase of light tar yield indicate that Ni/Al 2 O 3 can catalyze tar cracking, which is consistent with the literature . Ni is also the active site for dehydrogenation and hydrogenation, which is favorable for the generation of H 2 , as shown in Figure c. In addition, the increase of water conversion confirms the role of Ni/Al 2 O 3 in catalysis of SCC.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the reduction peaks of nickel species in 7 Ni/AC catalyst, it can be seen that three obvious reduction bands are observed: the first band (I) at the lowest-temperature with a maximum around 228-231 ∘ C can be assigned to the well dispersed nickel species in the samples (may be assigned to the relatively free nickel species weakly interacting with support), which are easily reduced [29]. The low temperature band, the second band (II), shows a maximum at about 275-290 ∘ C, which may be due to the reduction of dispersed nickel species [55] and the third band (III) with a maximum around 343-357 ∘ C may be related to the reduction of bulk nickel species in intimate contact with the support [56]. The peak positions and their contribution are summarized in Table 3.…”
Section: The Reduction Of Ni Species In Ni-ac Catalystsmentioning
confidence: 98%
“…At the same time, thermodynamic and kinetic analysis of mild and deep hydrogenation also confirm the above conclusion. 25 Therefore, lower reaction temperature, lower reaction pressure and higher space velocity should be adopted on the premise of achieving the basic requirements.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%